Evaluation of Organochlorine Pesticide Residues in a Farmland in Abuja, Nigeria - Dan-kishiya, A.S.; Mofio, B.M.; Oko, V.E.; Okolo, J.C.; Isah, A. (Direct Research Journal of Biology and Biotechnology, 2023)
This study conducted an extensive assessment of organochlorine pesticide residues in a farmland located in Abuja, Nigeria. Employing Gas Chromatography-Mass Spectrometry, the concentrations of these pesticide residues were determined in soil samples. The recovered residues include Alpha Lindane, Beta Lindane, Heptachlor, Aldrin, DDT and Endrin Aldehyde. The study unveiled notable fluctuations in pesticide concentrations across the sampling period. In May, the highest concentrations were observed for Endrin Aldehyde (45.932 mg/kg) while the lowest concentration was recorded for Aldrin (0.33 mg/kg) in January. These findings bear ecological and health implications, potentially impacting biodiversity, human health and soil physicochemical properties. Furthermore, it is noteworthy that the concentrations of pesticide residues in the study surpassed the maximum residue limits (MRLs). This research provides crucial insights into the presence and levels of organochlorine pesticide residues in Abuja’s agricultural soils, emphasizing the urgent need for robust pesticide management and control measures within the region.